The art of Islamic banking and finance : tools and techniques for community-based banking - Abdul-Rahman, Yahia, 1944- (Hoboken, N.J. : Wiley, 2010)
"A detailed look at the fast-growing field of Islamic banking and finance The Art of Islamic Banking and Finance is a modern American take on what it means to incorporate Islamic finance principles into everyday banking and investment techniques by introducing a new brand of banking for all people of all faiths: The Riba-Free (RF) banking. The author is considered the father of RF (Islamic) banking in America. He has been a banker and an Imam/scholar for over 40 years in America since 1968. He started the tedious process with a finance company, LARIBA, in Pasadena, California in 1987. This is the first book ever in the field to trace the origins of prohibiting the renting of money at a price called interest rate and over-indulging in debt. The book reviews in great details the theological foundations of prohibiting interest in the Jewish Bible, the Christian Bible, and the Qur'aan. The author then discusses money and how fiat money is created, the role of the Federal Reserve, and the banking system in America. The book also discusses for the first time ever how to include an important aspect of RF (Islamic) finance using commodity indexation and marking the items to be financed to market in order to avoid participating in economic "bubbles." The author discusses how these rules work, how they affect consumer behavior, and how they change the role of the banker/financier. Covers a new pioneering model that is based on the Law (Shari'aa) and how it is applied in every transaction from joint ventures and portfolio management to home mortgages and personal financing. Shows how to incorporate the Law (Shari'aa) into American financing and banking systems. Points to RF (Islamic) finance and banking as a way to emphasize socially responsible investing The Art of Islamic Banking and Finance also includes a discussion on the emergence of a culture of RF (Islamic) banking and finance today, which is based on the real Judeo-Christian-Islamic spirit and very effective when compared to twentieth-century models that use financial engineering and structuring techniques to circumvent the Law (Shari'aa). The book also includes case studies based on the actual experience of the author and detailed analysis of the superior results realized by applying this new brand of banking to financing"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Banks and banking -- Islamic countries; Finance -- Islamic countries. -- MIS, General